Micro and mesoporous materials based on zeolite Y for the florol synthesis via the prins cyclization of isoprenol - Demuth, Pascal (Elsevier, 2025)
Several parents and Sn-modified microporous and mesoporous catalysts were investigated in Prins cyclization of isoprenol with isovaleraldehyde for the production of the desired cis isomer of pyranol, Florol ® using dimethylcarbonate as a solvent in the temperature range of 30–60 °C. The highest selectivity to pyranols, 70% was obtained over microporous Sn-Y-80 (number denotes SiO2/Al2O3 ratio) at 40 °C, while 64% selectivity to pyranols was obtained at 99% conversion over dealuminated H-Y-80 exhibiting mesoporosity and low Brønsted to Lewis acid ratio of 0.16. For microporous catalysts even higher BA/LA ratio and large amounts of Lewis acid sites were beneficial, as was the case for H-Y-30 modified with SnCl2, because the reaction occurred mainly on the outer surface of the catalyst.